1995
DOI: 10.1007/bf01248374
|View full text |Cite
|
Sign up to set email alerts
|

Soft morphological filtering

Abstract: Abstract. Stack filters are widely used nonlinear filters based on threshold decomposition and positive Boolean functions. They have shown to form a very large class of filters which includes rank-order operations as well as standard morphological operations. The stack filter representation of an order statistic filter provides an efficient tool for the theoretical analysis of the filter.Soft morphological filters form a large subclass of stack filters. They were introduced to improve the behavior of standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 18 publications
(29 reference statements)
0
33
0
1
Order By: Relevance
“…From Figures 2b-d it is obvious that, as in gray-scale soft morphology, the greater the value of the order index, the better the detail preservation. Comparing Figures 2b-d, it can be also observed that the smaller the value of k, the closer the behavior of a vector soft morphological transform is to that of the corresponding vector standard morphological transform, just as in the case of soft gray-scale morphology (Kuosmanen and Astola, 1995). This is one more similarity of vector soft and gray-scale soft morphological transforms.…”
Section: Theorem Iii4 Extensivity-antiextensivity If the Origin Liesmentioning
confidence: 63%
See 2 more Smart Citations
“…From Figures 2b-d it is obvious that, as in gray-scale soft morphology, the greater the value of the order index, the better the detail preservation. Comparing Figures 2b-d, it can be also observed that the smaller the value of k, the closer the behavior of a vector soft morphological transform is to that of the corresponding vector standard morphological transform, just as in the case of soft gray-scale morphology (Kuosmanen and Astola, 1995). This is one more similarity of vector soft and gray-scale soft morphological transforms.…”
Section: Theorem Iii4 Extensivity-antiextensivity If the Origin Liesmentioning
confidence: 63%
“…Soft morphological operations are based on weighted order statistics and, therefore, algorithms such as mergesort and quicksort, which were developed for the computation of weighted order statistics, can be used for the computation of soft morphological filters (Kuosmanen and Astola, 1995). The average complexity of the quicksort algorithm is O (N log N), where N is the number of elements to be sorted (Pitas and Venetsanopoulos, 1990).…”
Section: Implementationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,10] In soft morphological operations the maximum or the minimum operations, used in standard morphology, are replaced by weighted order statistics.…”
Section: Grey-scale Morphologymentioning
confidence: 99%
“…The weights depend on the structuring element, which is divided into two parts : the core, the pixels that participate with weights greater than one, and the soft boundary, the pixels that participate with weights equal to one. It has been shown that soft morphological operations are less sensitive to additive noise and to small variations in object shape [10][11][12].…”
Section: Introductionmentioning
confidence: 99%